Pricing efficiency in livestock auction markets: A two‐tier frontier approach. (19th July 2022) - Verteramo Chiu, Leslie J.; Tauer, Loren W.; Gröhn, Yrjo T.
Abstract: We estimate the pricing efficiency of a livestock auction market using a two‐tier stochastic frontier model. This model captures pricing inefficiency of a hedonic pricing model for livestock via exponential error terms above and below the hedonic model specification. The direction of pricing inefficiencies, whether above or below the hedonic pricing model, represent surplus transfer from buyers to sellers or from sellers to buyers, respectively. Using data from a 7‐year period in a livestock auction market, we found that on average livestock buyers extract about 6% of surplus from sellers. That is, on average, livestock auction market underprices by about 6% below its full information price. Buyer concentration also affects the degree of surplus transfer. At low levels of buyer concentration, when the top four‐buyer market concentration is <30%, there is an overpricing of only 1.23% over the full information price, extracting surplus from buyers to sellers. At higher buyer concentrations, buyers can extract up to 7% of surplus from sellers.